Formulation and Evaluation Of Sheet Mask Essens From Cassava Leaf Extract (Manihot esculenta Crantz.) - Anggianingrum, Rafiah; Rahmawanty, Dina; Sari, Destria Indah (Jurnal Sains dan Terapan Kimia, 2024)
Cassava leaves are plants that contain flavonoids and vitamin C that can act as antioxidants to ward off oxidation reactions due to free radicals so that the benefits of cassava leaves can be formulated into topical preparation from such as cosmetics one of them as a sheet mask essence. This study aims to determine the characteristics of essence sheet mask cassava leaf extract. The preparation is made with as many 3 formulas, with cassava leaf extract concentrations of 1.0%(F1), 3.0%(F2), and 5.0%(F3). The research method used for the manufacture of essence preparation is to mix all the ingredients and add cassava leaf extract and perfume. The essence preparation is evaluated including organoleptic, pH, viscosity, and stability tests. The result of this study obtained a yellow-orange yellow essence, with a characteristic aroma of lemongrass oil and liquid consistency. An increase in the concentration of the extract results in a decrease in pH and an increase in viscosity. This study concludes that variations in the concentration of cassava leaf extract affect the physical characteristics of sheet mask essence preparations on the organoleptic test, pH, viscosity, and mechanical stability tests of the three formulas are unstable against pH and organoleptic test, and in the cycling test all formulas are also physically unstable to viscosity and pH tests.